Implementation of Character Education for Early Childhood through Habituation and Role Modeling at TK Mujahidin, Semarang Regency (International Forum of Researchers and Lecturers, 2025)
Character education in early childhood plays a central role in shaping moral integrity, civic responsibility, and a sense of national identity. In recent years, however, educators and policymakers have expressed growing concern regarding the increasing prevalence of behavioral issues among young children, such as bullying, disrespect, and lack of empathy. These challenges highlight the importance of consistent and systematic efforts in building strong character foundations during the early years of schooling. This study explores the implementation of character education at TK Mujahidin in Semarang Regency, with particular emphasis on two pedagogical approaches: habituation and role modeling. The research employed a qualitative descriptive method through interviews, observations, and documentation involving teachers, administrators, and parents. Findings indicate that core values—such as honesty, discipline, empathy, and responsibility—are effectively internalized when embedded into daily routines, including flag ceremonies, prayer practices, and classroom discipline. Teachers play an essential role not only as facilitators of instruction but also as role models, reinforcing values through consistent actions, language, and spontaneous interventions in children’s social interactions. Furthermore, character education is strengthened by integrating thematic and cultural content into lessons, as well as by fostering collaboration between schools, parents, and community stakeholders. This localized model demonstrates that character formation in early childhood is most effective when grounded in socially responsive and culturally relevant practices. The study contributes a replicable framework for educators and institutions seeking to strengthen character education in similar contexts. It also emphasizes that character-building is not a separate program but must be embedded holistically into the learning environment, teacher conduct, and home-school collaboration. By uniting habituation, modeling, and cultural integration, early education can nurture children who are disciplined, responsible, and empathetic, preparing them to become ethically grounded citizens